2003
DOI: 10.20506/rst.22.3.1435
|View full text |Cite
|
Sign up to set email alerts
|

The risk posed by the importation of animals vaccinated against foot and mouth disease and products derived from vaccinated animals: a review

Abstract: The Terrestrial Animal Health Code of the OIE (World organisation for animal health) (the Terrestrial Code) makes recommendations for international movements of live animals and animal products because of a possible generic risk of foot and mouth disease (FMD) for these different commodities. For instance, international movement of vaccinated live animals or products of such animals is restricted due to the possible masking of clinical disease as a result of vaccination and to the perceived risk of persistentl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
30
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(31 citation statements)
references
References 33 publications
(44 reference statements)
1
30
0
Order By: Relevance
“…Virus isolation from pig tonsils at day 26 postcontact confirmed that these animals had been infected without clinical symptoms of disease and that virus had persisted in them for 4 weeks. This case resembles what has been described as a carrier state of FMDV for cattle, sheep, and goats (2,39,46) but not yet demonstrated for pigs. Bottleneck transmission may confer on the virus the ability to ratchet down fitness and virulence to ensure the immunization of at least a fraction of the population rather than kill or debilitate the entire susceptible host population.…”
Section: ϫ4supporting
confidence: 81%
See 3 more Smart Citations
“…Virus isolation from pig tonsils at day 26 postcontact confirmed that these animals had been infected without clinical symptoms of disease and that virus had persisted in them for 4 weeks. This case resembles what has been described as a carrier state of FMDV for cattle, sheep, and goats (2,39,46) but not yet demonstrated for pigs. Bottleneck transmission may confer on the virus the ability to ratchet down fitness and virulence to ensure the immunization of at least a fraction of the population rather than kill or debilitate the entire susceptible host population.…”
Section: ϫ4supporting
confidence: 81%
“…The etiological agent FMD virus (FMDV) of Picornaviridae occurs as seven distinct serotypes and multiple subtypes, reflecting significant genetic and antigenic heterogeneity. In the field, this heterogeneity is reflected by the lack of cross-protection even between intraserotype variants (2,3,46). VP1 (1D), the highly variable FMDV capsid protein with roles in virus entry, immunity, and serotype specificity, has been the subject of extensive comparative sequence analysis (reviewed in reference 22).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…FMDV is the first disease for which the Office International des Epizooties (now World Organisation for Animal Health, OIE) established an official list of pathogen-free zones and countries. In the last decade, costly FMD outbreaks have occurred in Europe (United Kingdom and The Netherlands, 2001), Asia (India and Philippines, 1996; Taiwan, 1997; Korea, 2000 and 2002), South Africa (1999 and2000), and South America (Brazil and Argentina, 2001), resulting in the slaughter of a large number of animals as well as implementation of quarantine and decontamination procedures (38), with associated socioeconomic ramifications.…”
mentioning
confidence: 99%